THE EXPRESSION OF NATIONAL-CULTURAL CONCEPTS IN THE LINGUISTIC INTERPRETATION OF GAMES (Scientific journal of the Fergana State University, 2025)
This article discusses the necessity of investigating the national-cultural characteristics of linguistic units and the need to explore the relationship between language and culture, which has led to the formation of linguoculturology as a distinct field. It examines the characteristics of linguistic and cultural studies as an emerging area that studies the cultures of peoples expressing themselves in language and stabilizing as a specific form of human relationships.